Lakar Simpulan / Shafilla Subri and Wan Noor Faaizah Wan Omar - Subri, Shafilla; Wan Omar, Wan Noor Faaizah (Faculty of Art and Design, 2021)
The metaphor is one of the epistemologies that underline the beauty of language in linguistic aspects. Through language appreciation, there is a lot of beautiful advice and messages that are conveyed that affect our daily lives. In the Malay world, there are many methods of delivering massage and advice, including through poetry, idioms, proverbs and many more. However for this project we choose idioms as our piece of art. When we talk about idioms it not only focuses on Malay world, but every language in this world has its own idiomatic language, which is that the objective and order still have the elements of advice and unique message. Idioms also could express the wisdom of philosophy and common sense in our community to convey a specific message politely. Idioms also describe the implicit meaning and complex implicit meaning of figurative language, especially proverbs and their relation to the thought to be expressed. Some examples of Malay idioms which are “ buah tangan” means gift or souvenir, “ulat buku” means diligent reading, “hidung tinggi” means arrogant and many more.